Influence of the bud neck on nuclear envelope fission in Saccharomyces cerevisiae - Melloy, Patricia G. (Exp Cell Res, 2017)
Studies have shown that nuclear envelope fission (karyokinesis) in budding yeast depends on cytokinesis, but not distinguished whether this was a direct requirement, indirect, because of cell cycle arrest, or due to bud neck-localized proteins impacting both processes. To determine the requirements for karyokinesis, we examined mutants conditionally defective for bud emergence and/or nuclear migration. The common mutant phenotype was completion of the nuclear division cycle within the mother cell, but karyokinesis did not occur. In the cdc24 swe1 mutant, at the non-permissive temperature, multiple nuclei accumulated within the unbudded cell, with connected nuclear envelopes. Upon return to the permissive temperature, the cdc24 swe1 mutant initiated bud emergence, but only the nucleus spanning the neck underwent fission suggesting that the bud neck region is important for fission initiation. The neck may be critical for either mechanical reasons, as the contractile ring might facilitate fission, or for regulatory reasons, as the site of a protein network regulating nuclear envelope fission, mitotic exit, and cytokinesis. We also found that 77–85% of pairs of septin mutant nuclei completed nuclear envelope fission. In addition, 27% of myo1Δ mutant nuclei completed karyokinesis. These data suggested that fission is not dependent on mechanical contraction at the bud neck, but was instead controlled by regulatory proteins there.